Intervenção fonoaudiológica com familiares de crianças surdas - Nascimento, Gicélia Barreto (2015)
The language therapist work with deaf children relatives is important to provide exchange of experiences and strengthen relations among them. This type of intervention also aims to wrap the family in the therapeutic process. This research contemplated a more humanized approach to the clinical work performed by language therapists, since it addressed an integrated approach while focusing and promoting ways for active participation of the family throughout the therapeutic process. This study objectives were to investigate the perception and knowledge of deaf children relatives about the language development of their children; describe the pragmatic abilities of deaf children in everyday communication situations, from the point of view of relatives, and verify the effects of an intervention program focused on family in the linguistic interaction among deaf children and their relatives, as well as in the change of attitude in the communicative scene with the child. It is an exploratory research of qualitative and quantitative approach. It was divided into three stages: (i) interview with the participants, application of the protocol “Primeira Parte: Avaliação do Perfil Pragmático”, video recording of the familiar interaction between deaf child and listener relative; (ii) development of speech therapy, with family-centred approach, in 10 meetings per dyad, lasting 60 minutes each session; and (iii) reapplication of the procedures performed in the first stage, aiming to comparatively analyse the effects of the speech therapy performed. For the interviews data was used Content Analysis on topics. The pragmatic assessment analysis followed what was proposed by the used protocol. To analyse the videos was used the Eudico Linguistic Annotator (ELAN) software. Quantitative data were tabulated in a Microsoft Excel 2010 spreadsheet and statistically analysed by means of the STATISTICA 9.1 program. The study enrolled five children and five relatives. The average age of the relatives was 42 years, and of the children, four years. The children had sensorineural hearing loss in both ears, of varying degrees. Three of them had neurological impairment associated with hearing loss. The intervention was effective because, by comparing the data, a change was observed in the perception of the relatives about the language development and pragmatic abilities of the children. There was also an improvement in the interaction between the child-adult pairs after relatives participated in the proposed intervention.